Current and potential roles of archaeology in the development of cultural evolutionary theory. (5th April 2018) - Garvey, Raven
Abstract : Archaeology has much to contribute to the study of cultural evolution. Empirical data at archaeological timescales are uniquely well suited to tracking rates of cultural change, detecting phylogenetic signals among groups of artefacts, and recognizing long-run effects of distinct cultural transmission mechanisms. Nonetheless, these are still relatively infrequent subjects of archaeological analysis and archaeology's potential to help advance our understanding of cultural evolution has thus far been largely unrealized. Cultural evolutionary models developed in other fields have been used to interpret patterns identified in archaeological records, which in turn provides independent tests of these models' predictions, as demonstrated here through a study of late Prehistoric stone projectile points from the US Southwest. These tests may not be straightforward, though, because archaeological data are complex, often representing events aggregated over many years (or centuries or millennia), while processes thought to drive cultural evolution (e.g. biased learning) operate on much shorter timescales. To fulfil archaeology's potential, we should continue to develop models specifically tailored to archaeological circumstances, and explore ways to incorporate the rich contextual data produced by archaeological research. This article is part of the theme issue 'Bridging cultural gaps: interdisciplinary studies in human cultural evolution'.